The role of the digital economy on enabling sustainable agriculture: Evidence from One Belt One Road countries - Mihasina Harinaivo Andrianarimanana; Zhaohui Qin; Mirindra Finaritra Rabezanahary Tanteliniana; Zhihao Su (Cogent Food & Agriculture)
The digital economy and environmental sustainability are continuously becoming important components of every economic activity, including agriculture. Therefore, it is of utmost importance to investigate the mechanisms by which the digital economy ensures sustainable agriculture. This study investigates the relationship between the digital economy and sustainable agriculture in 57 one-belt-one-road countries between 2009 and 2020. We found that the digital economy failed to support sustainable agriculture for countries under the One-Belt-One-Road initiative. Moreover, even if the digital economy promotes rural revitalization, the characteristics of the rural population confound the expected positive effect of the digital economy on sustainable agriculture. However, the negative confounding effect of agricultural system diversification on sustainable agriculture is moderated by the production value of eco-friendly crops. The higher the productivity of eco-friendly crops, the more the digital economy can contribute to sustainable agriculture. Finally, the effect of the digital economy on sustainable agriculture differs according to economic level and localization.